Biogas digestate – benefits and risks for soil fertility and crop quality – an evaluation of grain maize response - Przygocka-Cyna Katarzyna; Grzebisz Witold (Open Chemistry, 2018)
The agricultural usability of biogas digestate solids (BDS) as a soil amendment depends upon its impact on soil fertility and the content of minerals in the edible part of the grown crop. This hypothesis was verified in a series of field experiments with maize conducted between 2014 and 2016 at Brody, Poland. The two-factorial experiment consisted of the DBS application method (broadcast and row) and its rate: 0, 0.8, 1.6, 3.2 t ha–1. The post-harvest analysis of soil fertility showed that BDS can, at least partly, replace mineral fertilizers. The supply of N-NO3 to maize as a growth driving factor was significantly limited by a shortage of iron, potassium and, to some extent, magnesium. As recorded in 2016, the shortage of available Fe resulted in a low/pool of N-NO3, thus significantly decreasing the yield of grain. The shortage of K supply to grain created a pathway for the accumulation of other elements, including heavy metals. The disadvantage of the N-NO3 pool increase, due to the DBS application, was concomitant with the enhanced intake of cadmium and lead, which consequently exceeded their permissible concentration limits in grain. These unfavorable results of biogas digestate impact on the quality of maize grain can be ameliorated by incorporating zinc into the biogas type of soil amendment and keeping a sufficiently high level of available potassium and iron. The shortage of K can be partly overcome by a better sodium supply, however, its accumulation in grain results in an enhanced accumulation of cadmium and lead.